Gold, silver & brass : jewellery of the Batak in Sumatra, Indonesia - Sibeth, Achim, 1954-; Wotzel, Jorg (Milan, Italy : 5 Continents Editions, 2012)
The first book to examine the rich jewellery traditions of the Batak people in Indonesia is a gorgeous tribute to a vanishing way of life.
Includes bibliographical references.
Keywords: Jewelry -- Indonesia -- Sumatra; Jewelry -- Southeast Asia; Batak (Indonesian people) -- Jewelry